Researching pedagogy and practice with Canadian mathematics teachers - Reid, David A. 1963-; Suurtamm, Christine; Savard, Annie; Simmt, Elaine; Manuel, Dominic; Borden, Lisa Lunney; Barwell, Richard (Research in mathematics education series., 2020)
"The past two decades have seen an increased interest in education, especially in core areas such as mathematics, language and science. This is in part a consequence of the increase in the number of international comparisons of educational outcomes, such as PISA and TIMSS. Much research has focused on the contributions that curricula, financial resources, parental support, and so on, might have on educational outcomes. A factor that seems likely to have a very significant effect on student achievement, teachers' practices and beliefs, has received little attention. This book reports results from a research program that sought to develop and employ research methods to compare teachers' practices and beliefs across Canada. It provides insight into the challenge of such research, and describes teachers' contexts, beliefs and practices, and how they differ, in four regions and across two languages. Using a multivocal ethnography approach (Tobin, 1999) teachers were involved in the preparation and discussion of videos of their own teaching and that of others. This approach resulted in not only insights into the teachers' pedagogies and practices, but also opportunities for the teachers to reflect on their own teaching in new ways, and for researchers to reflect on research practices and orientations. The work is innovative in several ways. In a field crowded with research on teachers' practices, beliefs and knowledge this research helps to unearth the implicit values that underlie the way teachers see teaching itself. Through the process of observation of each other's practice, the teachers became aware of their own pedagogies, giving them new insights into their values and practices. Researchers also engaged in a parallel process of reflection on their own practices as observers of teachers, with similar insights into the values guiding their work. This book will be of interest to government policy makers, teachers and teacher educators, as well as researchers in mathematics education. Members of the AERA SIG in Research in Mathematics Education, the Canadian Mathematics Education Study Group, the NCTM, and provincial mathematics teacher associations are potential readers"--